FUNCTIONS OF THE SUFFIX –MOST IN ENGLISH - Siboro, Efrika (UC Journal: ELT, Linguistics and Literature Journal, 2023)
This paper explored the functions of the suffix –most in English and the formation of new categories of the suffix -most by analyzing the words containing it. This quantitative descriptive study collected the data from Wordbyletter.com and the online Oxford English Dictionary (OED). The text-based document analysis examined 40 words having the suffix -most. Results showed that four functions of the suffix –most, namely to form: a noun into an adjective (25%), an adjective into an adjective (45%), an adverb into an adjective (15%), and a preposition into an adjective (15%). It was analyzed that the usage frequency of several words represents all the grammatical categories of the suffix –most based on the Corpus of Contemporary American English (COCA). Firstly, foremost functioning as noun formation occurred 7,078 times. Secondly, lowermost functioning as adjective formation occurred 40 times. Thirdly, the uppermost functioning as adverb formation appeared 532 times. Lastly, aftermost functioning as preposition formation occurred twice only.